Italicity as a cosmopolitan resource - Bechelloni, Giovanni (MATRIZes, 2007)
This article discusses the concept of Italianity, from phenomenology point and from the theory point. I am trying to deal with this subject so as to demonstrate its heuristic or educative potential to: (a) research the international and intercultural communication; (b) construct educational politics that lean to the formation of a new, responsible and inclusive cosmopolitanism; and (c) develop a wider and longer appreciation of war and peace subjects.